The Financial Performance of Regencies/Cities in South Sumatera Province (2006-2015 Time Period) - Rohima, Siti (AFEBI Economic and Finance Review, 2017)
This study is for observing the regional financial performance influence of regencies/cities in South Sumatera province. The research is implemented quantitatively by using the data panel double regression of the 2006 – 2015 time period. Regional financial performance covers fiscal decentralization, autonomy, effectiveness and efficiency. Based on a partial count, fiscal decentralization has a regression coefficient as large as 62.73185, which means fiscal decentralization has a positive and significant influence to economic growth. Then regional finance autonomy has a regression coefficient as large as -16.04656 which means that regional autonomy has a negative influence yet significant to economic growth. Observing from regional financial effectiveness which has a regression coefficient as large as -0.074855, which means that effectiveness has a negative influence and not significant to economic growth. Regional financial efficiency has a regression coefficient as large as -0.254122, which means that efficiency has a negative influence and not significant to economic growth. Based on the count as a whole it means that Fiscal Decentralization, Regional Finance Autonomy, Effectiveness, and Efficiency have significant influences to economic growth. This means regional financial performance is very influential to the economic growth of regencies/cities in South Sumatera Province in the 2006-2015 time period. JEL Classification: E02, H70, H77Keywords: Autonomy, Economic Growth, Effectiveness, Efficiency, Regional Financial Performance, Fiscal Decentralization